Eusebi Chronicorum libri duo - Eusebius (My University, 1866)
The Chronicon or Chronicle (Greek: Παντοδαπὴ ἱστορία Pantodape historia, "Universal history") was a work in two books by Eusebius of Caesarea. It contained a world chronicle from Abraham until the vicennalia of Constantine I in A.D. 325. Book 1 contained sets of extracts from earlier writers; book 2 contained a technically innovative list of dates and events in tabular format
Edited by Alfred Schoene. - Bertolini : Apud Weidmannos, 1866. - Text in latin and greek
Vol. 2 (1866 ; xlii, 236 pages) : Eusebi chronicorum canonum quae supersunt
Keywords: World history; History, Ancient; Armenia-History